Preliminary screening for microplastic concentrations in the surface water of the Ob and Tom Rivers in Siberia, Russia - Frank, Yuliya A.; Vorobiev, Egor D.; Vorobiev, Danil S.; Trifonov, Andrey A.; Antsiferov, Dmitry V.; Hunter, Soliman Tina; Wilson, Scott P.; Strezov, Vladimir (Sustainability, 2021)
This study characterizes the abundance and morphology of microplastics in surface water of the Ob River and its large tributary, the Tom River, in western Siberia. The average number of particles for two rivers ranged from 44.2 to 51.2 items per m3 or from 79.4 to 87.5 μg per m3 in the Tom River and in the Ob River, correspondingly. 93.5% of recovered microplastics were less than 1 mm in their largest dimension, the largest group (45.5% of total counts) consisted of particles with sizes range 0.30-1.00 mm.